Coping Strategies and Restrictions during COVID- 19 Pandemic: A Multimodal Discourse Analysis of Some Selected Cartoons and Comics - Hamdi Ebeid Khalil (Maǧallaẗ Kulliyyaẗ Al-ādāb Ǧāmiʿaẗ Būrsaʿīd, 2024)
With the advent of COVID-19 pandemic, the whole world is overwhelmed with a mood of fear, anxiety, depression and psychological discomfort. The Coronavirus has wrapped all aspects of life with a new mode so that the authorities concerned have imposed stay-at-home orders, curfews and restrictions on mass mobility and daily activities. These restrictions have given rise to unprecedented practices rarely available in pre-Coronavirus era. Consequently, the normal course of life has greatly changed and a new daily routine has been established during the COVID-19 pandemic whose impact on all life activities is characterized by being extensive and having far-reaching consequences. This paper investigates the COVID-19 repercussions in some purposively selected cartoons and comics from different websites. The selected cartoons and comics attempt to establish what may be called covidity, a neologism that requires collective and wide-spread response to the COVID-19 pandemic.  It analyzes negative pandemic-related aspects that have bearing especially on travel, religious and sport activities. The study draws upon Kress and Leeuwen’s approach of Visual Grammar (2006) within the framework of social semiotics. The study probes Multimodal Discourse Analysis (MDA), which is mainly applied and opted for deeper examination of visual discourse maintained in the data under discussion. Multimodality is a concept that accounts for different semiotic resources in communication to express certain meanings or ideologies. The paper demonstrates how coping strategies help to alleviate the grim mood created by the pandemic and to get adapted to new circumstances. مع ظهور جائحة كوفيد-19، ساد العالم أجمع حالة من الخوف والقلق والانزعاج النفسي. لقد أضفى فيروس كورونا نمطا جديدا على كافة مناحي الحياة، مما دفع السلطات المعنية لإصدار تعليمات البقاء بالمنازل وحظر التجول والقيود على التنقل الجماعي والأنشطة اليومية. وقد أدت هذه القيود إلى ظهور ممارسات غير مسبوقة قلما تواجدت في فترة ما قبل فيروس كورونا. وبالتالي، تغير المسار الطبيعي للحياة بشكل كبير وظهر روتين يومي جديد خلال جائحة كوفيد-19 والذي كان له تأثير بالغ المدى على جميع أنشطة الحياة. تبحث هذه الدراسة تداعيات كوفيد-19 في بعض الرسوم الكرتونية والرسوم المضحكة المختارة من مواقع الكترونية مختلفة. تهدف البيانات المختارة إلى إرساء ما يمكن تسميته "بالكوفيدية"، وهو مصطلح جديد يتطلب استجابة جماعية وواسعة النطاق لجائحة كوفيد-19، ويحلل الجوانب السلبية المتعلقة بالوباء وتأثيرها لا سيما على السفر والأنشطة الدينية والرياضية. تعتمد الدراسة على منهج كريس وليوين في القواعد النحوية المرئية (2006) في إطار نظرية السيمائية الاجتماعية. كما تبحث الدراسة في تحليل الخطاب المتعدد الوسائط والذي يتم تطبيقه بشكل أساسي في تحليل الخطاب المرئي بصورة أشمل للبينات قيد الدراسة. إن تعدد الوسائط مفهوماً يفسر الوسائل السيمائية المختلفة في التواصل للتعبير عن معاني أو أيدولوجيات معينة. وتكشف الدراسة عن مدى مساهمة تلك الاستراتيجيات في التخفيف من حالة التجهم التي خلّفها الوباء والتأقلم مع الواقع الجديد.